(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B;s (NrOMANY(B; (NpOWESTX (B/ s (N~ASTX (B1s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B: s (NpRAWDA(B, s, 1982)
(Nw PERWYJ TOM sOBRANIQ WO[LI PROIZWEDENIQ(B: "(NbEDNYE L@DI(B", "(NbELYE NO^I(B", "(NnETO^KA nEZWANOWA(B".s
rus
Keywords: (N|PISTOLQRNYJ ROMANs; (NpOWESTI I RASSKAZYs; (NsENTIMENTALXNYJ ROMANs